A Creative Approach: Enhancing Customer Engagement and Brand Growth during My Marketing Internship at Henkel Adhesives - Barad, Khushi (ATLAS SkillTech University, 2025)
The report titled “A Creative Approach: Enhancing Customer Engagement and Brand Growth during My Marketing Internship at Henkel Adhesives” presents an in-depth look at my enriching internship experience with Henkel Adhesives. This report details the key insights and practical skills I acquired during my summer internship, which was a crucial part of my second-year MBA studies at ATLAS SkillTech University. Throughout the internship, I engaged in various marketing activities, including conducting competitor analysis, compiling a strategic expo list, and overseeing the production of an animated video for a product. These tasks provided me with a thorough understanding of marketing strategies and customer interaction, effectively connecting theoretical knowledge with practical experience. With the support of my faculty mentor, Mukul Bhatt, I explored the intricacies of marketing within a leading global adhesives company. This opportunity allowed me to apply academic concepts to real-world situations, enhancing my abilities in market research, campaign execution, content development, and data analysis. The report underscores the importance of this hands-on experience in my professional development, demonstrating how it has aligned my academic background with industry demands. It offers a preview of the detailed findings and reflections included in the report, giving readers insight into the value and impact of this transformative internship at Henkel Adhesives.
Project Report on A Creative Approach: Enhancing Customer Engagement and Brand Growth during My Marketing Internship at Henkel Adhesives (2023-2025) Under the Guidance of Prof. Mukul Bhatt
Keywords: Marketing